Analisis Profesionalisme Guru di Era Post Pandemik Covid 19 dan Hubungannya dengan Prestasi Belajar Siswa - Ashari Husen; Wiwik Kusmawati (Universitas Insan Budi Utomo, 2022)
The purpose of this study is to determine the effect of teacher professionalism in the post-Covid 19 pandemic era on student achievement. In this research carried out using a type of descriptive correlational research. The sampling technique for this study used simple random sampling. Based on this study, a sample of 40 students in each class could be taken while for teachers there were 6 people. After that, samples were taken, namely the level of teacher education, teaching experience, professional development and level of knowledge about teacher professionalism. The results showed that there was a significant influence of teacher professionalism on student achievement.